AMPA receptor GluA1 Ser831 phosphorylation is critical for nitroglycerin-induced migraine-like pain. (1st May 2018) - Tang, Yuanyuan; Liu, Sufang; Shu, Hui; Xing, Ying; Tao, Feng
Abstract: Migraine is the third most common disease worldwide; however, the mechanisms underlying migraine headache are still not fully understood. Previous studies have demonstrated that α-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid (AMPA) receptor phosphorylation plays an important role in central sensitization of pain transmission. In the present study, we observed that AMPA receptor GluA1 Ser831 phosphorylation was enhanced in the spinal trigeminal nucleus caudalis (Sp5C) after intraperitoneal injection of nitroglycerin (NTG). The NTG injection induced acute migraine-like pain including photophobia and mechanical hypersensitivity as reported previously. Interestingly, targeted mutation of GluA1 Ser831 site to prevent phosphorylation significantly inhibited NTG-induced migraine-like pain. Moreover, NTG incubation caused a robust Ca 2+ influx in cultured brainstem neurons, which was dramatically inhibited by GluA1 S831A (serine at the 831 site of GluA1 is mutated to alanine) phospho-deficient mutation, and treatment with 1-naphthyl acetyl spermine (NASPM), a selective Ca 2+ -permeable AMPA receptor channel blocker, dose-dependently blocked the NTG-evoked increase of Ca 2+ influx in the cultured neurons. We further found that intra-Sp5C injection of NASPM significantly inhibited NTG-produced mechanical hypersensitivity. These results suggest that AMPA receptor phosphorylation at the Ser831 site in the Sp5C is critical for NTG-induced migraine-like pain. Highlights: Nitroglycerin enhances AMPA receptor GluA1 Ser831 phosphorylation in the Sp5C. Targeted mutation of GluA1 Ser831 reduces nitroglycerin-induced migraine-like pain. GluA1 Ser831 phosphorylation in the Sp5C contributes to migraine-like pain.